Cyanoacrylate Glue Ablation for Symptomatic Reflux in a Duplicated Femoral Vein: A Case Report - Kilsoo Yie; Eun-Hee Jeong; A-Rom Shin; Bo-Mi Kim; Eun-Jung Hwang (Vascular Specialist International)
The literature on minimally invasive techniques specifically targeting reflux in symptomatic femoral vein duplication (FVD) is limited. We present a rare case of symptomatic reflux in FVD, successfully treated with cyanoacrylate glue ablation under ultrasonographic guidance. Our findings suggest that the unique anatomy of FVD can be effectively addressed through percutaneous endovenous glue ablation, providing a technically safe and feasible alternative without open surgery. Our patient experienced symptom resolution, no post-procedural complications, and maintained stable occlusion at a 1-year follow-up. This outcome highlights the potential of endovenous glue ablation as an innovative approach in managing deep vein reflux, particularly in cases involving FVD. To broaden its application in clinical practice, further research is crucial to establish appropriate patient selection criteria and refine treatment protocols.